Introduction to the special issue on L2 writing and feedback processing and use in pen and paper and digital environments: Advancing research and practice - Manchón, Rosa M.; Coyle, Yvette (Studies in Second Language Learning and Teaching, 2022)
The present special issue (SI) is a collection of position papers and empirical studies intended to advance disciplinary conversations on the learning and teaching of second or foreign language (L2) writing in instructed second language acquisition (ISLA) contexts. It does so by analyzing critically past research, providing new empirical insights obtained in controlled and classroom-based studies conducted in various educational settings with diverse populations, suggesting worthy avenues to be pursued in future research agendas, and drawing implications for practice.